Earned Value Management (EVM) as a Real-Project-Based Learning Resource in Construction Management: A Quantitative-Descriptive Study on a Revetment Construction Project - Rifana S. S. I. Kawet; Navel Oktaviandy Mangelep (Sakura Digital Nusantara, 2026)
Purpose: This study assesses the project performance of a revetment construction project at Manado Bay, Bersehati Market Complex (contract value IDR 11,120,996,728; duration 133 calendar days) using the Earned Value Management method, while examining its effectiveness as a real-project-based learning medium in the Construction Management course. Methods: A quantitative-descriptive approach using Earned Value Analysis was employed over 19 weeks, applying three primary EVM indicators BCWS, BCWP, and ACWP, from which SPI, CPI, and project completion projections (ETC, EAC, ETS, ECD) were derived from the project's BoQ, planned and actual S-curves, and weekly execution reports. Findings: At week 19, SPI = 2.6 (ahead of schedule) and CPI = 0.4 (severe cost overrun). EAC reached IDR 50,896,353,625.36 (≈4.6× the original budget); estimated completion is 167 days, exceeding the contract by 34 days. The paradoxical coexistence of high SPI and critically low CPI constitutes an educationally valuable scenario for analytical learning. Research Implications: Real project data has strong potential to strengthen students’ conceptual understanding of EVM, cultivate integrated data-interpretation skills, and build forecasting competencies aligned with construction industry demands. Civil engineering programs should systematically incorporate real project case studies supported by comprehensive assessment rubrics. Conclusion: EVM analysis of real government project data constitutes an effective and theoretically grounded PBL medium for Construction Management instruction, simultaneously developing technical competency and higher-order analytical thinking aligned with KKNI Level 6 and SN-Dikti requirements. Originality: This study is the first to integrate quantitative EVM project-performance analysis with a theoretically grounded pedagogical framework within a single coherent research design, addressing a gap in civil engineering education literature in Indonesia.